Evaluation of CK19 and VEGF gene expression, ki67 antigen, p53 protein, C-erb-B2, and their relationship in oral squamous cell carcinoma - Shen, Yuchen; Xu, Zhongqiang; Liu, Miaomiao; Piao, Songlin; Li, Jichen (Cellular and Molecular Biology, 2022)
Oral squamous cell carcinoma (OSCC) is one of the ten most common malignant tumors globally. This study aimed to evaluate the expression changes of Cytokeratin 19 (CK19), vascular endothelial growth factor (VEGF), P53, ki67, and c-ert-B2 in OSCC patients. For this purpose, 30 patients were selected as the case group and 30 healthy individuals as the control group. The expression of CK19 and VEGF genes in their blood serum was measured. Also, the expression of ki67, P53, and c-ert-B2 markers in squamous cell carcinoma was evaluated using immunohistochemistry. T-test was used to analyze the data. The results showed that the presence of CK19 marker in people with OSCC was positive in 17 out of 30 patients and VEGF marker in 23 out of 30 patients. The mean of ki67 positive, P53 positive, and Cerb-B2 positive cells were 399.4, 221.4, and 26.8, respectively. The correlation test between the indices showed a statistical correlation between the incidence of ki67 and P53 (r = 91.5% and p = 0.02). While statistical correlation was not seen between the incidence of ki67 and Cerb-B2 index (r = -1.7% and p = 0.97) and P53 and C-erb-B2 index (r = -13% and p = 0.8) (p <0.05). In general, the expression of VEGF and CK19 genes is higher in patients with OSCC than in healthy individuals. Therefore, examining the expression level of these two biomarkers in the blood of OSCC patients can be considered as a diagnostic screening method in the early stages of the disease. The immunohistochemical study of squamous cell carcinoma can also be used as a diagnostic screening test in the early stages of the disease.